Integer linear programming on preference maximized of workforce scheduling - Mohd Razali, Siti Noor Asyikin; Mei, Fen Looi; Arbin, Norazman; Khamis, Azme (COMPUSOFT, 2018)
This study investigated the application of integer linear programming with the purpose of solving workforce scheduling problems in real life and satisfying the constraints at the same time, which includes the staff preferences towards shift and company policies. Integer linear programming is a well-known mathematical approach which is able to obtain the optimal solution faster than manually schedule construction in a less-complex way. In this study, a weekly schedule which involved thirteen staff is obtained successfully by using integer linear programming approach through the help of LP Solve IDE software. The result showed that the total staffing cost was successfully minimized due to reduced number of full shift assigned to staff. In addition, the staff satisfaction is maximized by satisfying all their preferences.